2020
DOI: 10.21037/atm-20-3033
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the management of congenital cataract

Abstract: Congenital cataract is a rare eye disease, one of the leading treatable causes of low vision in children worldwide. Hereditary cataracts can be divided in syndromic and non-syndromic cataracts. Early diagnosis in congenital cataracts is key to reach good visual function. Current surgical techniques, that combine microincision cataract extraction and primary intraocular lens (IOL) implantation, have improved childhood cataract outcome. Complications include posterior capsule opacification (PCO), aphakic or pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Microincision cataract aspiration combined with posterior capsulotomy, anterior vitrectomy, and primary intraocular lens (IOL) implantation is now recognized as the optimal surgical option for a large part of pediatric cataracts. 2 Prenatal demonstration of bilateral congenital cataracts in conjunction with congenital strabismus is a rare and unique combination of ocular abnormalities that has not been previously reported. Both anomalies can be diagnosed by prenatal ultrasound and the experienced ultrasound examiner should be familiar with obtaining views of the orbits and lenses.…”
Section: Congenital Strabismusmentioning
confidence: 98%
See 1 more Smart Citation
“…Microincision cataract aspiration combined with posterior capsulotomy, anterior vitrectomy, and primary intraocular lens (IOL) implantation is now recognized as the optimal surgical option for a large part of pediatric cataracts. 2 Prenatal demonstration of bilateral congenital cataracts in conjunction with congenital strabismus is a rare and unique combination of ocular abnormalities that has not been previously reported. Both anomalies can be diagnosed by prenatal ultrasound and the experienced ultrasound examiner should be familiar with obtaining views of the orbits and lenses.…”
Section: Congenital Strabismusmentioning
confidence: 98%
“…Congenital cataracts may also impair lens growth, eyeball axial length and refractive properties, all leading to visual disturbances. 2 The reported incidence varies depending on geographical location with an incidence of 1-6 cases per 10,000 live births in industrialized countries, which increases to 5-15 per 10,000 in underdeveloped regions of the world. 3 In one study, 1027 cases of congenital/infantile cataract were analyzed resulting in 36% of cases being unilateral and 64% with bilateral presentation.…”
mentioning
confidence: 99%
“…As cataracts can completely obscure vision by opacifying the lens, removal of symptomatic cataracts is recommended to restore vision in the affected eye(s) and prevent amblyopia in younger patients. Patients with significant congenital cataracts should pursue surgery as soon as possible, ideally within the first 6 weeks of life [ 116 , 117 ]. Patients younger than 6 months will typically receive aphakic contact lenses to replace their natural lens rather than an intraocular lens, as is standard for older children and adults.…”
Section: Cataractsmentioning
confidence: 99%
“…Despite this, the visual outcomes of cataractous patients vary greatly, ranging from useful visual acuity to blindness ( 2 , 3 ). Previous studies have suggested that cataract type ( 3 ), age at cataract extraction ( 4 ) and compliance with amblyopia therapy ( 5 ) are important determinants of visual outcomes for patients with CCs. Recently, it was also reported in unilateral CC patients’ affected eyes had greater foveal retinal thickness than their healthy fellow eyes ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%